Does equity risk premium puzzle exist in Philippines? - Moron, Katherine Villalobos (Animo Repository, 2015)
This paper aims to investigate the existence of equity premium puzzle in one of the developing countries, the Philippines. It has employed three methods to test this phenomenon, (1) basic model consumption of Mehra and Presscot (1985) and simplified model by Ni( 2006); (2) calibration (Campbell, 2003) and (3) GMM estimation (Hansen, 1982) using E-views. The calibration method results suggest that the puzzle exists in the country. However, due to the negative risk aversion accounted from the first and third method, it implies that there is no puzzle. This is difficult to accept since the rational reason behind this negative value is in fact that covariance between the consumption growth and stock return is negative. This denotes that equity premium puzzle might be solved by another puzzle involved in this correlation and can be verified depending on the method employed.